(Dis)advantaged positions in accessing gender-affirming healthcare in Finland: an intersectional qualitative study of foreign-origin transgender people - Mercédesz Czimbalmos; Shadia Rask (BMC, 2022)
Abstract Background An increasing body of scholarship focuses on transgender individuals' experiences when accessing gender-affirming healthcare. However, the experiences of transgender individuals who identify as being of foreign-origin in Finland have rarely been studied. This study aims to fill the gap in research and contribute to the understanding of the experiences of transgender individuals who also identify as belonging to the foreign-origin populations in Finland. Methods Fourteen semi-structured qualitative interviews were conducted and analyzed with reflexive thematic analysis (RTA), through the framework of intersectionality. The interviews were part of a broader sample of qualitative data, collected about the experiences of sexual and gender minorities among the foreign-origin populations in Finland. Results The analysis showed two main interconnected themes. Firstly, perceived barriers when accessing gender-affirming care. In this theme, the intersections of transgender identity, foreign background, class, and age affected the experiences of the individuals. Secondly, the necessity of "performing identities:" the intersections of class, transgender identity, nativity, and race affected those. Conclusion The findings of the current study suggest that the intersectional aspects of individual identities create structural inequalities in the Finnish gender-affirming healthcare system. To tackle these inequalities, further research is needed on the healthcare experiences of gender minorities in Finland both within and outside the scope of transgender-specific healthcare.